Evaluation of results-based financing in the Republic of the Congo: a comparison group pre–post study. Issue 3 (16th January 2018) - Zeng, Wu; Shepard, Donald S; Rusatira, Jean de Dieu; Blaakman, Aaron P; Nsitou, Bernice M
Abstract: Results-based financing (RBF) has been advocated and increasingly scaled up in low- and middle-income countries to increase utilization and quality of key primary care services, thereby reducing maternal and child mortality rates. This pilot RBF study in the Republic of the Congo from 2012 to 2014 used a quasi-experimental research design. The authors conducted pre- and post-household surveys and gathered health facility services data from both intervention and comparison groups. Using a difference-in-differences approach, the study evaluated the impact of RBF on maternal and child health services. The household survey found statistically significant improvements in quality of services regarding the availability of medicines, perceived quality of care, hygiene of health facilities and being respected at the reception desk. The health facility survey showed no adverse effects and significantly favourable impacts on: curative visits, patient referral, children receiving vitamin A, HIV testing of pregnant women and assisted deliveries. These improvements, in relative terms, ranged from 42% (assisted deliveries) to 155% (children receiving vitamin A). However, the household survey found no statistically significant impacts on the five indicators measuring the use of maternal health services, including the percentage of pregnant women using prenatal care, 3+ prenatal care, postnatal care, assisted delivery, and family planning. Surprisingly, RBF was found to be associated with a reduction of coverage of the third diphtheria, pertussis, and tetanus immunization among children in the household survey. From the health facility survey, no association was found between RBF and full immunization among children. Overall, the study shows a favourable impact of an RBF programme on most, but not all, targeted maternal and child health services. Several aspects of programme implementation, such as timely disbursement of incentives, monitoring health facility performance, and transparency of using funds could be further strengthened to maximize RBF's impact.